Risikofaktoren für die Entwicklung einer postoperativen Niereninsuffizienz in der aorto-koronaren Bypasschirurgie : eine retrospektive Analyse - Hauptmeier, Tim; Justus Liebig University Giessen (My University, 2011)
In dieser Studie wurde retrospektiv eine Datenanalyse von 1071 Patienten durchgeführt, bei denen Im Zeitraum Januar 2003 bis Dezember 2004 der Eingriff einer aorto-koronaren Bypass-Operation im Universitätsklinikum Gießen vorgenommen wurde. Es wurde untersucht, welche Risikofaktoren für das Auftreten einer postoperativen Niereninsuffizienz bestehen.Bei 1071 Patienten entwickelten 3.5% (n=37) eine postoperative Niereninsuffizienz. Es fand sich keine siginifikante Korrelation zwischen einer postoperativen Niereninsuffizienz und des BMI (p=0.444). Ebenfalls keine siginifikanten Unterschiede zeigten sich bei der Hauptstammstenose (p=0.725), der präoperativ bekannten Nierenfunktion (p=0.462), pAVK (p=0.157), Verweildauer (p=0.465), Art. Hypertonus (p=0.582), Hypercholesterinämie (p=0.303), Diabetes mellitus (p=0.418), Nikotinabusus (p=0.384). Weibliches Geschlecht ist in dieser Studie ein unabhängiger Risikofaktor für die Entstehung einer postoperativen Niereninsuffizienz (p=0.008). Höheres Lebensalter prädisponiert deutlich für die Entstehung eines postoperativen Nierenversagens (p=<0.001). Im Notfall durchgeführte aorto-koronare Bypass-Operationen zeigen eine signifikante Abhängigkeit (p=0.006). NYHA-Stadium IV bedeutet ein deutlich erhöhtes Risikoprofil (p=<0.001). 16.2% der Niereninsuffizienzgruppe waren Patienten mit 1-KHK Gefäßerkrankung. Es besteht eine hochsignifikante Abhängigkeit (p=<0.001). Sowohl präoperativ bekannte Herzrhythmusstörungen wie Vorhofflimmern (p=0.003) als auch postoperatives Kammerflimmern (p=<0.001) sind in dieser Studie Risikofaktoren für die Entstehung einer postoperativen Niereninsuffizienz. In unserem Patientenkollektiv zeigen Patienten mit bekannten cerebrovaskulären Ereignissen (p=0.035), Sepsis (p=<0.001) und der Verwendung von Katecholaminen (p=<0.001) siginifikante Unterschiede. Signifikante Abhängigkeiten zeigten sich ebenfalls in der Operationsdauer (p=0.008), Bypass-zeit (p=0.04) und dem Drainageblutverlust (p=0.003).In unserer Studie verstarben während des Krankenhausaufenthaltes 3.6% des Patientenkollektivs. 51.4% der Niereninsuffizienzgruppe waren verstorbene Patienten. Es besteht eine hochsignifikante Abhängigkeit (p<0.001).Auf unsere Studie bezogen, ist unsere Vergleichsgruppe der postoperativ niereninsuffizienten Patienten als eine signifikante Risikogruppe für eine höhere Mortalität und für postoperative Komplikationen anzusehen.

This is a retrospective study of 1071 patients, which had an aorto-coronary bypass surgery in the time period of January 2003 till December 2004 at the Justus Liebig University in Gießen. We investigated the risk factors of occurrence of postoperative renal insufficiency in patients undergoing coronary bypass surgery.To address this question we compared two patient groups (renal insuffiency vs. no renal insuffiency). 3.5% (n=37) out of 1071 patients developed postoperative renal insuffiency with an significant increase of creatinine levels of more than 100 % higher compared to baseline. The Body mass index (BMI) did not show a significant correlation to renal insuffiency (p=0.444). Also in our patient cohort a left main coronary artery stenosis of 50% or higher did not show a significant correlation to renal insuffiency (p=0.725). When we grouped the patients by their preoperative kidney function, we did not discover a significant difference (p=0.462). Patients with a known peripheral artery occlusive disease (p=0.157), were not more likely to develop a renal insufficiency. The patients that developed renal insufficiency stayed on average 3 days longer in the hospital than other postoperative patients (p=0.465). In our patient cohort, arterial hypertension (p=0.582), high cholesterol levels (p=0.303), diabetes mellitus (p=0.418), cigarette smoking (p=0.384) had also not a significant correlation to postoperative renal insuffiency. Female patients developed statistically significant more often renal insufficiency compared to males (p=0.008). Moreover, older age is an independent risk factor for the progression into renal insufficiency (p=<0.001). Emergency surgery showed an increased possibility of renal insuffiency (p=0.006). Furthermore, NYHA-stage IV patients are also at significantly higher risk to develope renal insuffiency (p=<0.001). In addition, 16.2% of the patients with postoperative renal insuffiency were patients with 1-coronary heart disease (1-CAD) and showed a significant correlation (p=<0.001).Moreover, cardiac dysrhythmias including preoperative atrial fibrillation (p=0.003) and postoperative ventricular fibrillation (p=<0.001) did increase the risk to develop renal insuffiency Patients with known cerebral insults (p=0.035), sepsis (p=<0.001) and the use of inotropic substances (p=<0.001) were more likely to develop a renal insufficiency. In our study we did observe a significant correlation between the CPB-time (p=0.04), operation time (p=0.008) and the rate of drainage-bloodloss (p=0.003) and developing a renal insuffiency.3.6% of the patients in our cohort died during their stay in the hospital. 51.4 % of of the group that had developed a renal insuffiency, were patients, who did not survive the operation (p=<0.001).Therefore our study clearly indicates that patients with postoperative renal insuffiency are at a significant increased risk of mortality and postoperative complications.
Keywords: postoperative Niereninsuffizienz; aorto-koronare Bypasschirurgie; ddc:610